Cyclic neutropenia complicated by renal AA amyloidosis - Metin, Ayşe; Ersoy, Fügen; Tınaztepe, Keriman; Beşbaş, Nesrin; Tezcan, İlhan; Sanal, Özden (The Turkish Journal of Pediatrics, 2000)
Cyclic neutropenia is a rare disease characterized by regular cyclic fluctuations in the numbers of neutrophils. Patients with the disease suffer from recurrent infections at regular intervals of nearly three weeks. Recently, recombinant human granulocyte colony-stimulating factor (rhG-CSF) was reported to be an effective treatment for this disease. Here we describe a 17-year-old cyclic neutropenic female patient with a very rare association of renal amyloidosis of AA type who was under intermittent rhG-CSF treatment for the previous one and a half years. We conclude that although the disorder is usually benign, reactive amyloidosis may rarely develop in cases who remain untreated for a long period of time. However familial Mediterranean fever (FMF) type II should also be born in mind, particularly in predisposed populations.
Keywords: cyclic neutropenia; AA type amyloidosis; renal; childhood